1994
DOI: 10.1093/occmed/44.2.91
|View full text |Cite
|
Sign up to set email alerts
|

α-Amylase hypersensitivity in non-exposed millers

Abstract: Occupational hypersensitivity to alpha-amylase among bakers and workers in the pharmaceutical industry has been described. We present the results of skin tests and in vitro methods used to assess alpha-amylase sensitivity in 259 millers. There was no occupational contact with the enzyme in this population. Positive skin tests to this allergen were obtained in 16 subjects (6.18 per cent), specific IgE values were found in seven subjects (2.7 per cent), specific IgG was detected on 45 workers (17.37 per cent) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another potential confounder is exposure to fungi in the bakeries. In a study of wheat millers, Moneo and coworkers (34) suggested that sensitization for fungal a -amylase could have been caused indirectly by A. oryzae growing on milled wheat because of cross-reactivity between this fungus and a-amylase (14). It is our opinion, however, that this phenomenon has not biased our study results.…”
Section: Discussionmentioning
confidence: 68%
“…Another potential confounder is exposure to fungi in the bakeries. In a study of wheat millers, Moneo and coworkers (34) suggested that sensitization for fungal a -amylase could have been caused indirectly by A. oryzae growing on milled wheat because of cross-reactivity between this fungus and a-amylase (14). It is our opinion, however, that this phenomenon has not biased our study results.…”
Section: Discussionmentioning
confidence: 68%
“…Previously, we described α-amylase hypersensitivity in nonexposed millers [15]. Although there was no occupational contact with the enzyme, workers were sensitized to A. oryzae α-amylase caused by a sensitization to Aspergillus and other molds contaminating cereal grains or flour.…”
Section: Discussionmentioning
confidence: 99%